Dexamethasone‐eluting Vascular Stents. (9th March 2013) - Hämäläinen, Mari; Nieminen, Riina; Uurto, Ilkka; Salenius, Juha‐Pekka; Kellomäki, Minna; Mikkonen, Joonas; Kotsar, Andres; Isotalo, Taina; LJ, Teuvo Tammela; Talja, Martti; Moilanen, Eeva
Abstract Percutaneous transluminal angioplasty (PTA) with stenting is widely used in the treatment of vascular disorders, but restenosis remains a significant problem. Drug‐eluting stents (DES) have been developed as an attempt to reduce the intimal response leading to restenosis. Drugs used in DES include mainly immunosuppressive and anti‐proliferative compounds. Glucocorticoids are also an interesting possibility for those purposes because they have anti‐proliferative effects in vascular smooth muscle cells and down‐regulate the production of cytokines and growth factors driving inflammation and fibrosis. In this MiniReview, feasibility and safety of drug‐eluting metal and biodegradable vascular stents are discussed with special emphasis on dexamethasone‐eluting stents.